(untitled) (Global Journal of Computer Science and Technology, 2023)
This paper first describes the blockchain technology is the current national support for new technologies has an important position in the national development strategy then combined with the national accounting development plan it analyzes the opportunities and challenges faced by the accounting information system and the theoretical basis and advantages of the integration of blockchain technology and accounting information system Finally the path of blockchain enabling accounting information system is analyzed